1992
DOI: 10.1029/91jb02508
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐ocean ridge magma chambers

Abstract: Geophysical evidence precludes the existence of a large, mainly molten magma chamber beneath portions of the East Pacific Rise (EPR). A reasonable model, consistent with these data, involves a thin (tens to hundreds of meters high), narrow (<1–2 km wide) melt lens overlying a zone of crystal mush that is in turn surrounded by a transition zone of mostly solidified crust with isolated pockets of magma. Evidence from the superfast spreading portion of the EPR suggests that the composition of the melt lens is mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
521
1
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 799 publications
(549 citation statements)
references
References 130 publications
(96 reference statements)
24
521
1
3
Order By: Relevance
“…Occurrences on these ridges are usually associated with propagating rifts or other small non-transform offsets. Sinton and Detrick [1992] [1984] suggested that variability in 87 Sr/86Sr correlates inversely with spreading rate, (although a more recent study did not support this finding [White et al, 1987]). …”
Section: Spreading Rate and Global Chemical Variabilitymentioning
confidence: 65%
“…Occurrences on these ridges are usually associated with propagating rifts or other small non-transform offsets. Sinton and Detrick [1992] [1984] suggested that variability in 87 Sr/86Sr correlates inversely with spreading rate, (although a more recent study did not support this finding [White et al, 1987]). …”
Section: Spreading Rate and Global Chemical Variabilitymentioning
confidence: 65%
“…[Sinton and Detrick, 1992]. If the duration of uninterrupted amagmatic episodes correspondingly increases, we expect that the longevity of detachment faults and thus the frequency of megamullion formation will also increase.…”
Section: Discussionmentioning
confidence: 99%
“…However, this definition seems physically unrealistic, at least for the narrow (<200 m) axial troughs on the EPR. The latest geophysical models envision the "magma chamber" beneath the EPR as a thin lens of mostly liquid magma (< 100-500 m thick and 1-2 km wide, at 1-2 km depth) over a more extensive body of partial melt and crystal mush [Sinton and Detrick, 1992]. The size and shape of the narrow axial troughs (Figure 9a) are inconsistent with the notion of them forming by magma withdrawal from the much wider and deeper magma lens, which would form a wider, more circular or elliptical depression at the surface [Ryan et al, 1983].…”
Section: -15 M (Table 2) This Comparison Suggests That Dikeinducedmentioning
confidence: 99%